Eksplorasi Peran Handphone Berbasis Android Dalam Pembelajaran Daring di Sekolah Dasar - Mohamad Sakban; Padlurrahman, Padlurrahman; Rismarini Nursaly, Baiq (PINUS: Jurnal Penelitian Inovasi Pembelajaran, 2021)
Learning activities in schools since the spread of the Covid-19 pandemic that hit the world, as a result of which learning is carried out online. However, in the era of globalization, such as at this time android-based mobile phones can be used as online learning media. So the purpose of this study is to see the role of Android-based mobile phones in online learning in elementary schools. The research method used in this study is a survey method in which the researcher took 2 samples of schools in Aikmel sub-district with a total of 105 students as respondents. The data collection technique used a questionnaire or a questionnaire consisting of 5 statement items and one conclusion statement item. The power analysis used in this research is descriptive analysis. The results showed that the role of cellphones in the learning process was less effective, but on the other hand, cellphones were very helpful in implementing online learning